Zoonotic gastrointestinal parasite burden of local dogs in Zaria, Northern Nigeria: Implications for human health - Christopher I. Ogbaje (International Journal of One Health, 2015)
Background: Zoonotic gastrointestinal parasites of dogs are of the global problem particularly in the developing countries. Dogs are the most common pet animals worldwide and have been reported to be hosts of many intestinal parasites of zoonotic importance globally. In Nigeria, gastrointestinal helminthes of dogs is currently endemic in 20 of the 36 states. Aim: In general, dogs are the closest animals to humans and for that reason we decided to carry out a survey study to check the incidence of these parasites in dogs and to ascertain the level of environmental contamination in the study area. Materials and Methods: Fecal samples were collected from dog patients presented to small animal clinic of Veterinary Teaching Hospital of Faculty of Veterinary Medicine, Ahmadu Bello University Zaria, dog’s fecal droppings from the streets, and residential Quarters of the University and gastrointestinal tracts (GIT) of dogs from dogs slaughtering house at Basawa Barrack, Zaria. Three methods were used in the analysis of the samples; simple flotation, sedimentation, and GIT processing methods within 48 h of collection. Results: Out of 224 samples analyzed 76(33.9%) were positive of at least one of the parasites. Of the 101 samples from streets and residential quarters of ABU, Zaria, Isospora spp. 12(11.9%) recorded the highest prevalence rate followed by Taenia spp. 6(5.9%), then Toxocara canis, Ancylostoma caninum, and Dipylidium caninum were 5.0%, 4.0%, and 1.0%, respectively. Isospora spp. (19.0%) recorded the highest prevalence rate for the 100 samples collected from small animal clinic. Other parasites encountered were T. canis (8.0%), A. caninum (8.0%) and Taenia spp. (5.0%). Parasites observed from the 23 gastrointestinal contents from “dog slaughtered houses” were T. canis (17.3%), Isospora spp.(13.1%) and A. caninum (4.3). Conclusion: The study revealed that zoonotic gastrointestinal parasites of dogs are endemic in Zaria and the general public in the area are at high risk of being infected with these parasites.However, there are no statistically significant differences in the level of zoonotic parasitic infestation in the three sample sites at p<0.05.